Using microcomputers and mainframes for data analysis in the social sciences - Greenberg, Barry (Columbus : Merrill Publishing Company, 1987)
This book is designed for graduate and advanced undergraduate students from disciplines, such as education, sociology, social work, psychology, nursing, marketing, and public administration, which typically include a research requirements.
Chapter 1. Using the computer for data description -- Chapter 2. Data base management -- Chapter 3. The use of correlation as research strategy -- Chapter 4. One-way tests of significance and research strategy -- Chapter 5. Multifactor test for significance -- Chapter 6. Using the computer to perform multiple regression.
Includes bibliographical references and index.
Keywords: MICROCOMPUTERS; COMPUTER PROGRAM LANGUAGES